The Western Ontario Meniscal Evaluation Tool Translated Into Italian Is a Reliable, Precise, and Responsive Patient-Reported Outcome Measure for Arthroscopic Meniscal Surgery - Michelangelo Palco, M.D.; Gabriele Giuca, M.D.; Giorgio Gasparini, M.D.; Roberto Simonetta, M.D.; Danilo Leonetti, M.D.; Filippo Familiari, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2025)
Purpose: To translate and culturally adapt the Western Ontario Meniscal Evaluation Tool (WOMET) into Italian to examine its reliability, measurement precision, and responsiveness in patients undergoing arthroscopic meniscal surgery. Methods: Patients with magnetic resonance imaging–confirmed meniscal injuries completed the Italian WOMET at baseline and again at 3 and 6 months postoperatively. The translation followed established guidelines for cross-cultural adaptation, including forward-backward translation and cognitive debriefing. Test-retest reliability was assessed using the intraclass correlation coefficient, and measurement precision was evaluated by calculating the standard error of measurement and the minimal detectable change. Responsiveness was measured via the standardized response mean. The Knee Injury and Osteoarthritis Outcome Score 4 questionnaire was administered for comparison. Results: A total of 97 patients (mean age, 38 years; age range, 22-58 years) were included. The Italian WOMET showed excellent test-retest reliability (intraclass correlation coefficient, 0.87). The standard error of measurement was 109.68 points, and the minimal detectable change was 307 points, indicating a high level of precision for detecting true clinical changes. The standardized response means were 1.94 at 3 months and 2.44 at 6 months, indicating strong responsiveness. A high correlation (r = 0.85, P < .001) with the Knee Injury and Osteoarthritis Outcome Score 4 supported concurrent validity. Conclusions: The Italian WOMET is a reliable, precise, and highly responsive patient-reported outcome measure for assessing health-related quality of life in patients undergoing arthroscopic meniscal surgery. Clinical Relevance: Given the increasing prevalence of meniscal injuries in Italy and the need for culturally relevant diagnostic tools, the validation of the WOMET in Italian is important for patients, health care providers, and scientists.